The patient with hypothyroidism in the Doctor's Office Item - Anna Fabian-Danielewska; Inga Janik; Agata Wawryków; Mirela Niedzielska; Katarzyna Korabiusz; Anita Liput-Sikora (Kazimierz Wielki University, 2017)
Hypothyroidism is a common form of endocrinopathy, it can be a problem for up to 10% of population. Women are five times more likely to suffer from thyroid diseases, and the frequency of morbidity raises with age. Family doctor in Poland is able to perform TSH, FT3, FT4 examination, and thyroid ultrasound when it comes to thyreology. It allows to treat patients with hypothyroidism, however it does not allow to precisely determine the cause. In order to determine the cause, family doctor needs to consult endocrinologist. Symptoms of hypothyroidism are not specific and rarely make patients inclined to visit the doctor. Treatment of hypothyroidism consists of L-thyroxine substitution in a certain dose. It is recommended to treat subclinical hypothyroidism with small doses of L-thyroxine when level of TSH > 10 mIU/L. When concentration level of TSH is lower than 10 mIU/L it is vital to individually assess risk factors and patients clinical situation. Decision whether to start the treatment should be made on those grounds.